EPJ quantum technology - Società italiana di fisica; EDP Sciences; Springer (Firm) (Heidelberg, Germany : Springer-Verlag, GmbH, 2014)
Covers theoretical and experimental advances in subjects including but not limited to the following: quantum measurement, metrology and lithography; quantum complex systems, networks and cellular automata; quantum electromechanical systems; quantum optomechanical systems; quantum machines, engineering and nanorobotics; quantum control theory; quantum information, communication and computation; quantum thermodynamics; quantum metamaterials; the effect of Casimir forces on micro- and nano-electromechanical systems; quantum biology; quantum sensing; hybrid quantum systems.
"A SpringerOpen journal."
Articles are added consecutively to the current annual volume.
Mode of access: World Wide Web.
Copublished by Societa Italiana di Fisica, EDP Sciences and Springer.
Description based on: Volume 1, issue 1 (December 2014); title from journal homepage (publisher's Web site, viewed January 30, 2014).
Latest issue consulted: Volume 5, issue 1 (December 2018) (Springer Link website, viewed May 4, 2018).
Keywords: Quantum theory -- Periodicals; Quantum computers -- Periodicals; Information theory -- Periodicals; Information theory; Quantum computers; Quantum theory; Atomic Physics; Electronic journals